Association of hematological indicies with diabetes, impaired glucose regulation and microvascular complications of diabetes - Demirtas, Levent (Int J Clin Exp Med, 2015)
In recent years, there has been renewed interest in hematological parameters as predictors of endothelial dysfunction and inflammation. The aim of our study is to evaluate the relationship between HbA1c and hematological indices, and to evaluate the relationship between these parameters and microvascular complications of diabetes. Three hundred and seven diabetic patients (124 male, 183 female; mean age 50.8±8.5), and 187 controls (76 male, 111 female; mean age 51.1±10.1) were included in the study. In the diabetic group, mean platelet volume (MPV), plateletcrit (PCT), platelet distribution width (PDW), white blood cell count (WBC), platelet count, platelet to lymphocyte ratio (PLR) and neutrophil to lymphocyte ratio (NLR) were significantly higher than the control group (P<0.05). Diabetic patients were divided into two group according to their HbA1c levels (Group 1; HbA1c <7 (n=82) and group 2; HbA1c ≥7 (n=225)). Mean platelet volume, PCT and PDW levels were significantly increased in group 2. Mean platelet volume was significantly increased in diabetic patients with retinopathy compared to those without retinopathy (P=0.006). The neutrophil to lymphocyte ratio and PLR levels were significantly higher in patients with nephropathy (P=0.004, P=0.004 respectively). There was statistically significant difference of lymphocyte count between patients with and without neuropathy. In correlation analysis, positive correlation between HbA1c and PCT (r(s)=0.192, P<0.001), HbA1c and PDW (r(s)=0.305, P<0.001), HbA1c and MPV (r(s)=0.352, P<0.001) were determined. In binary logistic regression analysis; WBC, PDW and PLR levels were found to be independently associated with diagnosis of diabetes while WBC, MPV, PLR and NLR levels were found to be independently associated with impaired glucose regulation. This study demonstrates that altered hematological indices are closely associated with HbA1c levels in individuals with and without diabetes and some of these parameters are associated with diabetic microvascular complications. These associations may be explained by connection between these easy accessible and inexpensive hematological indices and inflammation, tendency to coagulation and thrombosis in patients with diabetes.